Microvascular and Prognostic Effect in Lesions With Different Stent Expansion During Primary PCI for STEMI: Insights From Coronary Physiology and Intravascular Ultrasound - Li, Xida; Sun, Shuo; Luo, Demou; Yang, Xing; Ye, Jingguang; Guo, Xiaosheng; Xu, Shenghui; Sun, Boyu; Zhang, Youti; Luo, Jianfang; Zhou, Yingling; Tu, Shengxian; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background While coronary stent implantation in ST-elevation myocardial infarction (STEMI) can mechanically revascularize culprit epicardial vessel, it might also cause distal embolization. The relationship between geometrical and functional results of stent expansion during primary percutaneous coronary intervention (pPCI) is unclear. Objective We sought to determine the optimal stent expansion strategy in pPCI using novel angiography-based approaches including angiography-derived quantitative flow ratio (QFR)/microcirculatory resistance (MR) and intravascular ultrasound (IVUS). Methods Post hoc analysis was performed in patients with STEMI and high thrombus burden from our prior multicenter, prospective cohort study (ChiCTR1800019923). Patients aged 18 years or older with STEMI were eligible. IVUS imaging, QFR, and MR were performed during pPCI, while stent expansion was quantified on IVUS images. The patients were divided into three subgroups : over-expansion (>100%), optimal expansion(80%–100%), and under-expansion (<80%). The patients were followed up for 12 months. The primary endpoint included sudden cardiac death, myocardial infarction, stroke, unexpected hospitalization or unplanned revascularization, and all-cause death. Results A total of 87 patients were enrolled. The average stent expansion degree was 82% (in all patients),117% (over-expansion group), 88% (optimal expansion), and 75% (under-expansion). QFR, MR and flow speed increased in all groups after stenting. The overall stent expansion did not affect the final QFR(p=0.08) or MR(p=0.09),but it reduced the final flow speed (−0.14cm/s per 1%, p=0.02). Under- and over-expansion did not affect final QFR(p=0.17), MR(p=0.16), and flow speed(p=0.10). Cox analysis showed that stent expansion was not the risk factor for MACE(hazard ratio, HR=0.97, p=0.13). Over-expansion was an independent risk factor for no-reflow (HR=1.27, p=0.02) and MACE (HR=1.45, p=0.007). Subgroup analysis shows that mild under-expansion of 70%–80% was not a risk factor for MACE (HR=1.11, p=0.08) and no-reflow(HR=1.4, p=0.08); however, stent expansion <70% increased the risk of MACE (HR=1.36, p=0.04). Conclusions Stent expansion does not affect final QFR and MR, but it reduces flow speed in STEMI. Appropriate stent under-expansion of 70%–80% seems not to be associated with short-term prognosis, so it may be tolerable as non-inferior compared with optimal expansion. Meanwhile, over-expansion and under-expansion of <70% should be avoided due to the independent risk of MACEs and no-reflow events.